Advancing HIV Biomedical Prevention Research for At-Risk Adolescents. (15th December 2018) - Kapogiannis, Bill G.; Nelson, Robert M.; Siberry, George K.; Lee, Sonia; Hazra, Rohan
Abstract : Abstract: Despite significant additions to the HIV prevention toolbox, infection rates across the United States continue to rise among vulnerable adolescents and young adults. Access to these interventions by youth at risk for HIV is limited by the lack of data about their safety and use, compounding the myriad contextual barriers to effectively preventing HIV in this group. The NIH-funded Adolescent Trials Network implemented an innovative approach to the inclusion of adolescents at risk for HIV infection who consented for their own participation in the first adolescent study of HIV pre-exposure prophylaxis (PrEP). This model of mature minor consent was supported by state-based adolescent treatment statutes that extend an adolescent's ability to consent to participation in research with a sufficient prospect of clinical benefit from the intervention to justify the potential risks, and a balance of benefits and risks that is at least as favorable as available evidence-based alternatives. Important data on the safety and patterns of PrEP use by at-risk adolescents prompted the FDA to revise the label. The expanded indication of PrEP for HIV prevention in adolescents is hoped to inform clinical guidelines and provides a powerful tool to reduce new infections in the United States among vulnerable at-risk adolescents. Lessons learned from this years-long iterative endeavor have implications for improving access to the rapidly evolving landscape of HIV prevention modalities, including recently implemented studies of long-acting PrEP formulations designed to reduce the burden of daily adherence required by oral PrEP, a major clinical pitfall for adolescent clinicians and their patients.